The Relationship Between Social Support and Mental Health Degrees in Emerging Adulthood of Students - Arifin A. Pasinringi, Mayenrisari; Vanessa, Audrey Alya; Sandy, Grestin (Golden Ratio of Social Science and Education, 2022)
This study aims to examine the relationship between sources of social support and mental health degrees in emerging adulthood of Universitas Hasanuddin students. The participants of this research are undergraduate students at Universitas Hasanuddin. The sampling technique utilized in this research is stratified random sampling, while the number of the participants on this research is 411 participants. The scale applied in this study is the sources of social support scale adapted from the Multidimensional Scale of Perceived Social Support (MSPSS) (12 items, = 0.888) and the mental health degree scale adapted from the Mental Health Inventory (MHI-38) (24 items, = 0.941). The results showed that there is a significant relationship between sources of social support and mental health degrees in emerging adulthood of Universitas Hasanuddin students. The correlation level obtained based on the results of data processing shows that the Pearson Correlations value of the research variable of 0.445 is included in the moderate relationship criteria. A moderate relationship can be interpreted as a medium relationship obtained based on the correlation coefficient criteria. This shows that the relationship between the variables sources of social support and the variable mental health degree is in moderate criteria.